1999
DOI: 10.1111/j.1600-9657.1999.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro viability, mitogenicity and clonogenic capacity of periodontal ligament cells after storage in six different media

Abstract: The choice of storage medium for preserving traumatically avulsed teeth is important for the success of future replantation. The objectives of this study were to evaluate the effectiveness of six different media: culture medium, alpha minimal essential medium (alpha-MEM), milk, Hank's balanced salt solution (HBSS), ViaSpan and conditioned medium (CM) to preserve cultured periodontal ligament fibroblasts (PDLF). Periodontal ligament fibroblasts were obtained from explants of human healthy extracted teeth. Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 26 publications
6
123
0
7
Order By: Relevance
“…3,12 Respecto a la temperatura de transporte, los estudios no son concordantes; pues unos aconsejan conservar en leche a temperatura ambiente (20°C) y otros proponen leche fría (4°C) para mantener l a c a p a c i d a d c l o n o g é n i c a celular. 3,19,21,22,27 Leche evaporada entera 6,1 313 1 25…”
Section: Medios De Almacenamiento Y Transporte Para Dientes Avulsionadosunclassified
“…3,12 Respecto a la temperatura de transporte, los estudios no son concordantes; pues unos aconsejan conservar en leche a temperatura ambiente (20°C) y otros proponen leche fría (4°C) para mantener l a c a p a c i d a d c l o n o g é n i c a celular. 3,19,21,22,27 Leche evaporada entera 6,1 313 1 25…”
Section: Medios De Almacenamiento Y Transporte Para Dientes Avulsionadosunclassified
“…They were promising concerning the organization of collagen fibres and the number of viable cells. Some suggest that they can be perfect media for storing avulsed teeth but they need additional studies [4,6,[18][19][20][21]. Some considered milk as a gold standard for transporting avulsed teeth.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it contains many Minerals (Ca mg 33, Fe mg 0.39, Mg mg 6, P mg 74, K mg 114, Na mg 78 & Zn mg 1.18) and Vitamins (Thiamine mg 0.012 & Riboflavin mg 0.088). The pH of milk is about (6.5-7) and its osmolality is about (290-375 mOsm/kg) [4,18,30].…”
Section: Egg Whitementioning
confidence: 99%
“…While some demonstrated effectiveness for only up to 3 h (15,19) or 6 h (4), other showed effectiveness for 24 h (6,17,(20)(21)(22) or for up to 48 h (7,8). When culture plates were maintained at 20 °C and 37 °C, milk was the best storage medium for up to 48 and 24 h, respectively (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been some controversy (6,8), it has been suggested that milk with a lower fat content might be more appropriate to maintain PDLF viability than milk with a higher fat content (14). Previous studies indicate that cold milk is more effective than milk at room temperature (3,10,(15)(16)(17). Low temperatures have the advantage of reducing cellular metabolism (18) and limiting bacterial growth (3), which may affect the prognosis of tooth replantation.…”
Section: Introductionmentioning
confidence: 99%